2005
DOI: 10.1097/00124784-200501000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Architectural Environment in Community Health

Abstract: This discussion reports the status of a 12-year program administered by a statewide health agency to strategically assess, redevelop, and monitor the architectural and facility management performance of its network of community-based public health care facilities. A protocol, the Strategic Facility Improvement initiative, has directly resulted in significant improvements to the major share of a network of over 100 community clinic and clinical support facilities in the State of Louisiana. The SFI initiative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Environmental aspects of psychiatric settings and their effect on treatment outcome have been studied, but the greatest interest has been put on the psychosocial environment (Alden, 1978;Collins et al, 1985;Eklund & Hansson, 1997), while the effects of the physical environment have generally been disregarded within the psychiatric field (Verderber & Kimbrell, 2005). Knowledge concerning the effect of the physical environment in supported housing for the psychiatrically disabled has, in a literature review, been found to be very limited (Johansson, 2007).…”
mentioning
confidence: 99%
“…Environmental aspects of psychiatric settings and their effect on treatment outcome have been studied, but the greatest interest has been put on the psychosocial environment (Alden, 1978;Collins et al, 1985;Eklund & Hansson, 1997), while the effects of the physical environment have generally been disregarded within the psychiatric field (Verderber & Kimbrell, 2005). Knowledge concerning the effect of the physical environment in supported housing for the psychiatrically disabled has, in a literature review, been found to be very limited (Johansson, 2007).…”
mentioning
confidence: 99%